Endothelial Dysfunction in Diabetes: The Role of Protein Kinase C - Khamaisi, Mogher; Raz, Itamar (Vascular Disease Prevention (Discontinued), 2006)
Dysfunction of the vascular endothelium is considered to be a major risk factor associated with cardiovascular complications in patients with diabetes types I and II. Furthermore, vascular complications are the leading cause of mortality in diabetic patients. However, the mechanism by which endothelial dysfunction occurs remains obscure. Two systems have been implicated in the pathogenesis of endothelial dysfunction, including a decrease in the availability of nitric oxide (NO), a critical endothelium-derived vasoactive factor with vasodilatory and anti-atherosclerotic properties and/or enhanced action of vasoconstrictors such as endothelin-1. Chronic hyperglycemia is a major initiator of diabetic vascular complications. The mechanisms by which hyperglycemia causes vascular dysfunction are probably multiple. Such mechanisms include non-enzymatic glycosylation, oxidative stress, alteration of polyol-myoinositols, and activation of diacylglycerol (DAG) and protein kinase C (PKC) pathways. The initial studies of PKC activation in diabetes focused on microvascular complications, but there is accumulating evidence that PKC plays a role in several mechanisms promoting atherosclerosis. This review summarizes the current data that implicate PKC in promoting endothelial dysfunction mechanisms and microand macrovascular disease in diabetic patients.
Keywords: endothelin converting enzyme